Determination of vertical derivative of gravity anomalous by upward continuation and Taylor series transform methods: application to the Southwest sub-basin of the East Vietnam Sea - Nguyen, Nhu Trung; Tran, Van Kha; Bui, Van Nam (Vietnam Journal of Marine Science and Technology, 2022)
The vertical derivative of the gravity anomaly has a vital role in the methods of geological structure research such as determining fault systems and the location of the field sources. In addition, the vertical derivative is also used to calculate the downward continuation and further clarify the image of the seabed topography. However, determining the vertical derivative according to the traditional Fast Fourier Transform (FFT) method is often unstable and has low accuracy in high-order derivatives for high noise actual data. In this article, we introduce a new calculation method to determine the vertical derivative of gravity anomaly giving higher stable and accurate than traditional methods. The method is verified on synthetic model data and actual data of the Southwest sub-basin of the East Vietnam Sea.